INFORMATION SUPPORT OF BORDER CONTROL AT THE AIR BORDER CROSSING POINTS ACROSS THE STATE BORDER OF UKRAINE - Kushnir, Iryna; Kuryliuk, Yurii; Filippov, Stanislav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to investigate the features of information support at air border crossing points across the state border of Ukraine. Research methods: dialectical, structural-functional, comparative, etc. Results: features of information support at air border crossing points have been determined, ways of improvement of information support are offered. Discussion: the content of information support has been clarified, the foundations of information support have been determined, etc. Information support of border control at air border crossing points across the state border of Ukraine provides for specific information, data on the procedure, grounds for border procedures, aggregate information (preliminary one, provided by the air carrier and direct one, received during the border control) about passengers, information resources in which information about passengers, passport documents, etc. is processed and stored. Thus, the analyzed information support of border control at air border crossing points allowed to identify the possibility of processing preliminary information about passengers crossing the state border of Ukraine. There is currently no such possibility at border crossing points of other types of communication, which emphasized the peculiarity of the study. It has been determined that the systems of simplification of formalities also have a positive effect on security. For example, the purpose of data collection in the EU is to effectively combat illegal migration and strengthen border control, as well as to prevent, detect, investigate and prosecute terrorist and serious crimes. This applies to both the Passenger Information System (API) and additional passenger data, such as Passenger Name Record (PNR) data. There is no doubt that the successful application of API and PNR data exchange depends on a unified approach of all participants in information relations (both border agencies and airlines in different countries) regarding the question of data standard and standard of their transmission. Ensuring such a unified approach is a problem even when there is unity of legal regulation on data format and data exchange procedures. There are no special regulations in the national legislation that would regulate the relationship regarding the circulation of passenger registration data, nor is there a specific entity that processes this type of information. Thus, there is a need for special legal regulation of the circulation of information about airline passengers crossing the state border of Ukraine. In particular, the legislation must regulate the procedure, grounds, purpose of obtaining, processing, transmission, storage and destruction of information about passengers (its content), protection of the right to confidential information of persons operating international flights, establish a responsible controller of such information.